Genetic manipulation of anti-nutritional factors in major crops for a sustainable diet in future - Duraiswamy, Aishwarya; Sneha A., Nancy Mano; Jebakani K., Sherina; Selvaraj, Sellakumar; Pramitha J., Lydia; Selvaraj, Ramchander; Petchiammal K., Indira; Kather Sheriff, Sharmili; Thinakaran, Jenita; Rathinamoorthy, Samundeswari; Kumar P., Ramesh (Frontiers in Plant Science, 2023)
Consuming healthy food is now predominantly focused on by people across countries for strengthening their immune system. This is essential to tackle the emerging pandemic concerns. Moreover, this paved way for diversifying human diets by incorporating underutilized crops which are highly nutritious and climate-resilient in nature. Although this enables the nutritional uptake in foods, on the other end the bioavailability of the nutrients and their absorption from foods plays an essential role in curbing malnutrition across developing countries. This leads the research programs to focus on the antinutrients that interfere with the digestion and absorption of nutrients and proteins from foods. Antinutritional factors in crops like phytic acid, gossypol, goitrogens, glucosinolates, lectins, oxalic acid, saponins, raffinose, tannins, enzyme inhibitors, alkaloids, BOAA, and HCN are synthesized in crop metabolic pathways and they are interconnected with other essential growth regulation factors. Hence, breeding for a complete reduction of these factors tends to compromise the other desirable features like yield and seed size. However, advanced techniques aiming at breeding for improving negatively correlated traits with integrated multi-omics, RNAi, gene editing, and genomics-assisted breeding would open new strategies to handle these traits in crop improvement programs. Also, there is a need to emphasize individual crop-based approaches in upcoming research programs to achieve smart foods with minimum constraints in future. Therefore, this review focuses on the progress and prospects of molecular breeding approaches to improve nutrient bioavailability in major crops.